Analisis Kompetensi Supervisor Dalam Bidang Pai Di Sma Negeri 17 Kota Palembang - Yesi Arikarani (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2016)
The school supervisor or supervisor, as one element of education personnel, became the spearhead for the creation of the quality of education that qualified. Ideally the duties of a school superintendent is very good and noble. The school supervisor in charge of academic and managerial oversight of the designated schools through monitoring, assessment, and coaching as well as reporting and follow-up. And it will only be realized if an educational unit under the guidance of a good supervisor. To determine the competence of supervisors in the field of PAI in SMA Negeri 17 Palembang then we need to know to comply with standards of school supervisor he National Education Minister Regulation No. 12 of 2007 on Standards for School / Madrasah and National Education Minister Regulation No. 13 Year 2007 on Standards for School / Madrasah, the scope of supervision of education that the author is limited to the three competence of supervisors that supervise the managerial, academic supervision and supervision personality. Supervisory managerial managerial supervisory observation focuses on aspects of management and administration of the school.